Pelatihan Pembuatan dan penyusunan Bahan Ajar Berbasis Digital Menggunakan Aplikasi Blendspace untuk Menunjang Pembelajaran Bagi MGMP IPS Lampung Timur - Ekwandari, Yustina Sri; Sinaga, Risma Margaretha; Imanita, Myristica; Saputra, Cheri (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2022)
The purpose of this service is to improve the quality of teachers and teachers through the creation and preparation of digital-based teaching materials with blendspace applications. Blendspace is a web application that can make it easy for teachers to create and compile digital or electronic learning materials so that they can create a fun and orderly learning atmosphere. In the era of digitalization, all aspects have used technology networks including education. Therefore, teachers must be able to adapt to improve competence so that learning runs optimally and in accordance with the times. In addition, to maximize student learning, teachers must be able to provide a learning platform for students that can be accessed freely, such as providing digital-based learning materials so that students can study material anywhere and anytime. However, in reality there are still many teachers who have limited abilities and knowledge about the learning process that utilizes technology. As faced by the Social Studies MGMP teachers in East Lampung Regency who have difficulty in making and compiling digital-based teaching materials. Therefore, dedication to the creation and preparation of digital-based teaching materials using the blendspace application to support learning for MGMP Social Studies teachers in East Lampung district needs to be held in order to create quality learning. the method of implementing this service is socialization, training and evaluation. The resulting output target is the ability of MGMP Social Studies teachers in East Lampung Regency in creating and compiling digital-based learning materials using the blendspace application.Key words: Keywords: Digital-based Teaching Materials, preparation of teaching materials, online learning, Blendspace Applications